Si Doping-Induced Electronic Structure Regulation of Single-Atom Fe Sites for Boosted CO2 Electroreduction at Low Overpotentials - Cao, Changsheng; Zhou, Shenghua; Zuo, Shouwei; Zhang, Huabin; Chen, Bo; Huang, Junheng; Wu, Xin-Tao; Xu, Qiang; Zhu, Qi-Long (Research (Washington), 2023)
Transition metal-based single-atom catalysts (TM-SACs) are promising alternatives to Au- and Ag-based electrocatalysts for CO production through CO2 reduction reaction. However, developing TM-SACs with high activity and selectivity at low overpotentials is challenging. Herein, a novel Fe-based SAC with Si doping (Fe-N-C-Si) was prepared, which shows a record-high electrocatalytic performance toward the CO2-to-CO conversion with exceptional current density (>350.0 mA cm-2) and ~100% Faradaic efficiency (FE) at the overpotential of <400 mV, far superior to the reported Fe-based SACs. Further assembling Fe-N-C-Si as the cathode in a rechargeable Zn-CO2 battery delivers an outstanding performance with a maximal power density of 2.44 mW cm-2 at an output voltage of 0.30 V, as well as high cycling stability and FE (>90%) for CO production. Experimental combined with theoretical analysis unraveled that the nearby Si dopants in the form of Si-C/N bonds modulate the electronic structure of the atomic Fe sites in Fe-N-C-Si to markedly accelerate the key pathway involving *CO intermediate desorption, inhibiting the poisoning of the Fe sites under high CO coverage and thus boosting the CO2RR performance. This work provides an efficient strategy to tune the adsorption/desorption behaviors of intermediates on single-atom sites to improve their electrocatalytic performance.Transition metal-based single-atom catalysts (TM-SACs) are promising alternatives to Au- and Ag-based electrocatalysts for CO production through CO2 reduction reaction. However, developing TM-SACs with high activity and selectivity at low overpotentials is challenging. Herein, a novel Fe-based SAC with Si doping (Fe-N-C-Si) was prepared, which shows a record-high electrocatalytic performance toward the CO2-to-CO conversion with exceptional current density (>350.0 mA cm-2) and ~100% Faradaic efficiency (FE) at the overpotential of <400 mV, far superior to the reported Fe-based SACs. Further assembling Fe-N-C-Si as the cathode in a rechargeable Zn-CO2 battery delivers an outstanding performance with a maximal power density of 2.44 mW cm-2 at an output voltage of 0.30 V, as well as high cycling stability and FE (>90%) for CO production. Experimental combined with theoretical analysis unraveled that the nearby Si dopants in the form of Si-C/N bonds modulate the electronic structure of the atomic Fe sites in Fe-N-C-Si to markedly accelerate the key pathway involving *CO intermediate desorption, inhibiting the poisoning of the Fe sites under high CO coverage and thus boosting the CO2RR performance. This work provides an efficient strategy to tune the adsorption/desorption behaviors of intermediates on single-atom sites to improve their electrocatalytic performance.